Penyuluhan Pemanfaatan PLTS Mensuplai Beban Bohlam Lampu Kondisi Menyala Kepada Siswa SMA Bidang IPA - Parlindungan Pandapotan Marpaung; Adi Setiawan; Rizky Firmansyah (Yayasan Literasi Sains Indonesia, 2023)
This community service activity provided counseling to 24 class XII IPA1 students at Mater Dei High School, Pamulang sub-district, South Tangerang municipality. The counseling aims to know, understand and understand the use of PLTS using solar cells which produce a direct/DC output voltage to supply light bulbs when they are on. The counseling method for students to understand PLTS scientific material is theoretically presented in the classroom for 90 minutes. Then proceed to find out and understand the benefits of PLTS using solar cells to produce output voltage to supply light bulbs when they are on outside the classroom. The extension activity of illuminating the surface area of ​​solar cells with sunlight outside the classroom for 90 minutes is carried out by five (5) students per group taking turns accompanied by members of the extension team with the aim of practical knowledge and understanding. Each group of students takes an average of 16 minutes to shine sunlight on the surface area of ​​the solar cell which produces electrical power when the light bulb is on or off. The results of the implementation of counseling on the condition of the light bulb is on, the voltage value on the lamp load is Vb(lamp) = 4.46 volts when bright sunlight shines on the surface area of ​​the solar cell. Then, if the light bulb does not light up, the voltage value on the light load changes to 0.351 volts, when sunlight is blocked or blocked from reaching the surface area of ​​the solar cell. The results of the outreach activities were 24 students responding to six (6) questions with multiple choice answers listed on the questionnaire form that had been prepared. A total of 23 people chose useful answers to the content of the material presented, a total of 22 people chose interesting answers to questions about the material presented by the speaker and as many as 21 people chose useful answers for the entire extension activity event.